A Comparison of Different Tissues Identifies the Main Precursors of Volatile Substances in Chicken Meat - Luo, Na; Liu, Li; Yuan, Xiaoya; Jin, Yuxi; Zhao, Guiping; Wen, Jie; Cui, Huanxian (Frontiers in Physiology, 2022)
Amino acids and fatty acids are the main precursors of volatile organic compounds (vocs) in meats, but systematic research on their precursors is still lacking. Using the breast muscle tissue (BM, mainly composed of amino acids) and abdominal fat tissue (AF, mainly composed of fatty acids) of chicken as the as a comparison, we further identified the sources of vocs by a conjoint analysis of gas chromatography-mass spectrometry (GC-MS) and the untargeted metabolomics. The results exhibited every nine vocs in BM and AF tissue, containing the common Hexanal, Octanal and Nonanal. And then, the results showed that their contents of 1-Octen-3-ol, 2,4-Nonadienal,(E,E)-, Benzaldehyde and other vocs were higher in BM than in AF, but the contents of Heptacosane, Diethyl Disulfide, etc. were opposite in two tissues. In addition, the contents of Hexanal, Heptanal, Octanal, etc. had similar amounts in both tissues. Further, the analysis of the weighted co-expression network also explored the metabolites of vocs in BM of chicken. The results showed that the blue module in BM was significantly positively correlated with Hexanal, 2,4-Nonadienal, (E,E)- and Heptanal, and revealed L-Tyrosine, L-Asparagine, Adenosine, Valine were the main precursors of 2,4-Nonadienal, (E,E)- and Heptanal in BM. Therefore, we illustrated that amino acids are the main precursors of 1-Octen-3-ol, 2,4-Nonadienal, (E,E)-, Heptanal and other compounds. Fatty acids are the main precursors for Diethyl Disulfide. However, Hexanal may be formed from a combination of amino acids and a small number of fatty acids as precursors. These findings will help to understand the preconditions of vocs in chicken meat.